The effect of financial ratios on stock prices of consumer goods companies - Agustian Nugraha Putra; Zaharuddin Zaharuddin; Rhoma Iskandar (Goodwood Publishing, 2026)
Purpose: This study examines the effects of net profit margin, return on assets, and earnings per share on the stock prices of consumer goods companies listed on the Indonesia Stock Exchange during 2019–2024. This study also aims to address inconsistencies in previous findings and provide insights for investors and companies to make better financial and investment decisions. Research Methodology: This study employs a quantitative approach with secondary data sourced from the annual financial statements of 36 consumer goods companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2024. The analysis uses multiple linear regression to examine the effects of Net Profit Margin (NPM), Return on Assets (ROA), and earnings per share (EPS) on stock prices, with classical assumption tests ensuring data reliability before hypothesis testing. Results: The findings show that NPM and ROA have positive and significant effects on stock prices, while EPS has a significant negative effect. Conclusions: This study concludes that Net Profit Margin (NPM) and Return on Assets (ROA) positively influence stock prices, while earnings per share (EPS) negatively affects them, highlighting the complex relationship between profitability metrics and market performance. Limitations: The study's limitations include the exclusion of other potential influencing factors, such as liquidity, leverage, macroeconomic conditions, and market sentiment, which may also impact stock prices. Contributions: This study contributes to the understanding of how profitability indicators, particularly NPM and ROA, affect stock prices in the consumer goods sector, providing valuable insights for investors and financial analysts.